National Lung Cancer Screening: Recommended Age for Screening - Ramadhaniah, Fariha; Suzanna, Evlina; Syahruddin, Elisna; Shalmont, Grace; Rahayu, Pradnya Sri (Indonesian Journal of Cancer, 2024)
Indonesia, as a developing country, faces a significant burden of lung cancer, with the incidence and mortality rates ranking third. Unfortunately, the majority of patients are diagnosed at advanced stages of the disease. Indonesia has implemented a national cancer control program; screening and early detection are part of this program, which needs firm criteria to restrict the high-risk population due to limited resources. This article aims to recommend age criteria for National Lung Cancer Screening based on cancer registry data. We explore lung cancer screening policies across various countries, discuss the extent of the lung cancer burden and smoking prevalence as factors in determining age criteria for screening. Lung cancer is coded using ICD-O, third edition, C33–C34, and the incidence data were obtained from the Jakarta cancer registry. Data on the prevalence of smoking were obtained from national surveys and other research. Our review suggests that lung cancer screening should start at 35 years old, considering the distribution of lung cancer, the prevalence of smoking in Indonesia, as well as the carcinogenesis process of an individual when they start smoking.